APPLICATION OF GRAVITY GRADIENT METHOD AND 2-D MODEL ANALYSIS OF PALU - KORO AND JANEDO FAULT STRUCTURES, DOGGALA - CENTER SULAWESI - , Abdullah
Abstrak Two-dimensional modeling of Palu-Koro and Janedo fault structures was conducted based on gravity data using 2-D Talwani method. Two kinds of important information are employed to suppress model ambiguity i.e. fault parameters and geological data of Palu Valley area. These fault parameters are calculated using gradient method. The vertical gradient is obtained by applying Hilbert transform to horizontal gradient of gravity data. With these constraints the model can be considered sufficiently realistic and representative. The models obtained show that Palu valley has a complex geological structure and an intrusion of rock in the form of dike. Application of geological analysis to the first model, conclude that Metamorf Rock Complex and Tinombo Formation occured before the first crack of Palu-Koro fault took place. The second model shows that Metamorf Rock Complex, Tinombo Formation and Molasa sedimentation occured before Janedo fault happened. Application of regional tectonic analysis to the first model yield information about the Palu graben which was formed mostly due to the opening the Makassar Strait southeastward and the pressure of Banggai Sula microcontinent westward.